2017
DOI: 10.1039/c7ra02423a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient photocatalytic degradation of methylene blue by P2ABSA-modified TiO2 nanocomposite due to the photosensitization synergetic effect of TiO2 and P2ABSA

Abstract: A photocatalytic activity enhanced mechanism accounting for the photosensitization synergetic effect is proposed, with MB degradation pathways including chromophoric and auxochrome group degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(60 citation statements)
references
References 44 publications
3
45
1
Order By: Relevance
“…It can be observed that the characteristic peaks decreased with time while 665 nm peak shifted towards the blue region (hypsochromic effect). The blue shift in λmax suggested the stepwise removal of auxochromes (methyl or methylamine) [49,51]. As a result the degradation pathway of MB can be suggested to follow consecutive N-demethylation as reported also elsewhere in the literature [52].…”
Section: Photocatalytic Degradation Kinetics and Pathways Of Methylensupporting
confidence: 60%
See 1 more Smart Citation
“…It can be observed that the characteristic peaks decreased with time while 665 nm peak shifted towards the blue region (hypsochromic effect). The blue shift in λmax suggested the stepwise removal of auxochromes (methyl or methylamine) [49,51]. As a result the degradation pathway of MB can be suggested to follow consecutive N-demethylation as reported also elsewhere in the literature [52].…”
Section: Photocatalytic Degradation Kinetics and Pathways Of Methylensupporting
confidence: 60%
“…As a result the degradation pathway of MB can be suggested to follow consecutive N-demethylation as reported also elsewhere in the literature [52]. The electron donor properties of methyl groups facilitate the attack of • OH radicals for the demethylation pathway, which is considered to be an important step in the degradation of MB [49,51]. The intermediates can be identified based on the different absorption spectra characteristics as follows: azure B (λ max : 648-655 nm), azure A (λ max : 620-634 nm), azure C (λ max : 608-612 nm) and thionine or phenothiazine (λ max : 602 nm) [49].…”
Section: Uv-visible Lightmentioning
confidence: 70%
“…The addition of • OH radicals further eliminates NH 2 and SO 2 group from amino benzene sulphonic acid and converted this principal specie of MB dye to benzene sulphonic acid and phenol. Finally, MB dye containing aromatic rings is ruptured and readily converted to aliphatic acids, carbon dioxide, and water [14]. The TOC removal efficiency was found to be 66% at − 1.0 V vs. Hg/HgSO 4 in 30 min of electrochemical treatment.…”
Section: Demineralization Of Mb By Using Fe-based Gde Electrodesmentioning
confidence: 99%
“…O 2 − ). These holes reacted with H 2 O and hydroxyl anions to generate OH, which resulted in the degradation of MB molecules 65 . The band gap energy ( E g ) of TiO 2 , CuFe 2 O 4 , CuFe 2 O 4 @TiO 2 , and CuFe 2 O 4 @TiO 2 @CuBTC from UV–visible data and the Tauc plot method were 3.7, 1.4, 1.9, and 2.6 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%